1998
DOI: 10.1111/j.1472-8206.1998.tb00943.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant properties of calcium dobesilate

Abstract: Calcium dobesilate, a vascular protective agent, was tested in vitro for its scavenging action against oxygen free radicals. Calcium dobesilate was as potent as rutin to scavenge hydroxyl radicals (IC50 = 1.1 vs 0.7 microM, respectively). It was also able to scavenge superoxide radicals, but with 23 times less potency than rutin (IC50 = 682 vs 30 microM, respectively). Calcium dobesilate significantly reduced platelet activating factor (PAF)-induced chemiluminescence in human PMN cells and lipid peroxidation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…Deeper insights into the mechanism of action of CaD showed the beneficial effects of this drug as a result of its antioxidant properties, reflected particularly against the hydroxyl radical [36] and also by preventing the decrease in cellular antioxidant glutathione [37] . Its protective effects against diabetes-induced endothelial dysfunction appear associated with the decrease in advanced glycation end product levels and consequently to its antiangiogenic properties [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Deeper insights into the mechanism of action of CaD showed the beneficial effects of this drug as a result of its antioxidant properties, reflected particularly against the hydroxyl radical [36] and also by preventing the decrease in cellular antioxidant glutathione [37] . Its protective effects against diabetes-induced endothelial dysfunction appear associated with the decrease in advanced glycation end product levels and consequently to its antiangiogenic properties [38] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been also observed that elderly patients suffering from Alzeimer's disease showed reduction in symptoms upon chronic use of anti-inflammatory drugs 22 . It have been reported that Stevia rebaudiana have anti-inflammatory and antioxidant activity [23][24] . These anti-inflammatory and antioxidant effects may reduce brain damage and improve the neuronal functions of brain.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, aortae from both normal and diabetic rabbits exposed to elevated concentrations of glucose in vitro demonstrate impairment of endotheliumdependent relaxation [43]. Therefore, the antioxidant properties of DOBE [17,18] and its action on NO synthesis [22] could together constitute an additional mechanism explaining the beneficial effect of DOBE in restoring endothelium-dependent relaxation in aortae from diabetic animals to normal.…”
Section: Discussionmentioning
confidence: 99%
“…The main effect of the drug is to reduce microvascular permeability [16], leading to improved visual acuity. The pharmacological activity may be explained in part by the antioxidant properties of DOBE [17,18], through its action on the endothelium, which increases NO synthesis [15], and endothelium-dependent relaxation [18]. On the other hand, there is a disagreement about the possible effect of diabetes mellitus on vasoconstriction [19,20].…”
Section: Introductionmentioning
confidence: 99%